Shear Behavior of Small-Scale Continuous Hidden Beams Using Tied and Spiral Stirrups - Ahmed , Mostafa; Ekaputri, Januarti J.; Abdalla , Hany; Elgamal , Ahmed; Youssef , Ahmed (Civil Engineering Journal, 2026)
Hidden beams in reinforced concrete (RC) structures are widely used to meet architectural requirements; however, their reduced effective depth limits shear capacity. This study investigates the shear behavior of hidden beams reinforced with innovative rectangular staggered continuous spiral stirrups, addressing the absence of design guidelines for such reinforcement systems. Nine one-eighth-scale continuous beams were tested under two-point loading, with mortar used to reduce scale effects. The influence of the number, geometry, and configuration of spiral reinforcement was investigated. Both conventional and spiral stirrups significantly improved shear performance compared to the reference beam without transverse reinforcement (HB9-No). Beams with normal stirrups (HB1-N20, HB2-N30, HB3-N40, HB4-N50) increased shear capacity by 115%, 82%, 23%, and 4%, while spiral stirrup beams (HB1-S20, HB2-S30, HB3-S40, HB4-S50) achieved corresponding increases of 174%, 144%, 73%, and 27%, respectively. Overall, spiral reinforcement enhanced shear capacity and energy dissipation by approximately 30% and 46%, respectively, compared with conventional stirrups. Prototype capacities estimated using scaling relationships were compared with international design codes, which were found to be conservative. The findings demonstrate the effectiveness of spiral stirrups in improving shear strength and ductility and emphasize the need to include their contribution in future shear design equations for hidden beams.